In vitro hatching and maintenance of second stage larvae of Toxocara vitulorum - GHOSH, J D; BANERJEE, D P (The Indian Journal of Animal Sciences, 2013)
The tissue phase of Toxocara vitulorum cannot be diagnosed by conventional parasitological means. The present study was therefore aimed at developing an appropriate immunodiagnostic test. For this T. vitulorumeggs, collected from the faeces of infected buffalo calves and terminal portion of the uterus of adult female worms, were embryonated in 0.5% formalin at 28 oC for 20-30 days. Thick outer coats of the embryonated eggs were removed by treating with sodium hypochloride solution at 0.37Â°C for 4 hr. After removing the hypochlorite by 5 washings with sterile normal saline solution (NSS), decorticated eggs were vigorously shaken for 60 sec in a rubber-stoppered tube containing sterile sand and NSS. This process yielded more than 98% hatching of second stage larvae (L2)' Larvae were cleaned of shell-debris and dead/injured larvae by Baernannisation for 8 hr in antibiotic-antirnycotic added sterile Hank's Balanced Salt Solution with non-essential amino acids (HBSS-NEAA) using 3 layers of coarse cotton cloth. Out of the 4 media used for maintaining the larvae in vitro, RPMI-1640 could maintain more than 80% viable larvae for 28 days at 37oC and Eagle's Minimum Essential Medium with Hank's Salts (HMEM) for 21 days, In HBSSNEAA and NSS all larvae were dead by 72 and 24 hr respectively. This technique could be used to obtain T. vituiorum L2 for antigen preparations, and RPMI-1640 and HMEM may be used as maintenance media for L2.